2013
DOI: 10.1016/j.pain.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Emotional modulation of pain and spinal nociception in persons with major depressive disorder (MDD)

Abstract: Major depressive disorder (MDD) is associated with risk for chronic pain, but the mechanisms contributing to the MDD and pain relationship are unclear. To examine whether disrupted emotional modulation of pain might contribute, this study assessed emotional processing and emotional modulation of pain in healthy controls and unmedicated persons with MDD (14 MDD, 14 controls). Emotionally-charged pictures (erotica, neutral, mutilation) were presented in four blocks. Two blocks assessed physiological-emotional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…The present data on persons suffering from severe insomnia symptoms parallel those found in recent studies of fibromyalgia and major depressive disorder (17, 33). Specifically, all three groups failed to emotionally modulate pain, but had intact emotional modulation of NFR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present data on persons suffering from severe insomnia symptoms parallel those found in recent studies of fibromyalgia and major depressive disorder (17, 33). Specifically, all three groups failed to emotionally modulate pain, but had intact emotional modulation of NFR.…”
Section: Discussionsupporting
confidence: 89%
“…Given recent evidence that a failure to emotionally modulate pain (but intact NFR modulation) may be associated with chronic pain risk (17, 33, 34), we hypothesized that the insomnia group would exhibit disrupted emotional modulation of pain (i.e., a failure to observe a valence linear trend in pain), but intact NFR modulation. Given that physiological-emotional reactions were assessed in response to emotional pictures (i.e., valence ratings, arousal ratings, facial [corrugator] muscle activity, skin conductance, startle reflex modulation), a secondary goal was to assess group differences in emotional processing.…”
Section: Introductionmentioning
confidence: 99%
“…reported that antidepressants in the absence of diagnosed psychiatric disorders in patients with facial pain resulted in 81% being pain free, and minimal surgical intervention for facial pain was a positive predictor of pain relief. [9] In general, patients with any pain and comorbid MDD have a worse prognosis in pain control compared with patients without MDD;[1112161826282931] pain control appears to be more achievable when MDD is also under control in such patients. [151733] Nevertheless patients with psychiatric disorders more often seek care for somatic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Pain, an unpleasant sensory and emotional experience associated with actual or potential tissue damage [4], commonly co-occurs with negative affect [5,6]. In fact, research shows increased rates of comorbidity between chronic pain and depression and anxiety [7][8][9][10][11]. Psychological mechanisms that are relevant to the experience of pain and pain disorders are characterized by anxiety sensitivity (e.g., mental, physical, and social concerns) and illness/injury sensitivity (e.g., pain catastrophizing and fear of pain) [12,13].…”
Section: Introductionmentioning
confidence: 99%